Some Properties of Zero Forcing Hop Dominating Sets in a Graph (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we initiate the study of a zero forcing hop domination in a graph. We establish some properties of this parameter and we determine its connections with other known parameters in graph theory. Moreover, we obtain some exact values or bounds of the parameter on the generalized graph, some families of graphs, and graphs under some operations via characterizations.
Keywords: Zero Forcing Hop Dominating set; zero forcing hop dominating number